2018
DOI: 10.1039/c8tc00303c
|View full text |Cite
|
Sign up to set email alerts
|

Interface dipole for remarkable efficiency enhancement in all-solution-processable transparent inverted quantum dot light-emitting diodes

Abstract: We report our efforts to develop high performing all-solution-processable transparent inverted QD-LEDs by interposing an interface dipole between the ZnO ETL and the quantum dot light-emitting layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 41 publications
(36 reference statements)
2
31
0
Order By: Relevance
“…The ITO surface was modified by an ultrathin PFN-Br layer, prepared by spin coating at a rotation speed of 3000 rpm for 50 s followed by annealing at 90°C for 10 min. The use of PFN-Br-modified ITO anode is to create an interface dipole (25), assisting in bidirectional tunneling hole injection in the PM OPD. Then, a 300-nm-thick binary blend layer of P3HT: PC 70 BM (100:1) was deposited on the PFN-Br-modified ITO/glass substrates by spin coating at a rotation speed of 400 rpm for 100 s and annealing at 80°C for 20 s. A 320-nm-thick pristine P3HT optical spacer and a 500-nm-thick ternary blend layer of P3HT:PTB7-Th: PC 70 BM (70:30:1) were first coated on the precleaned silicon (Si) wafers, respectively.…”
Section: Device Fabricationmentioning
confidence: 99%
“…The ITO surface was modified by an ultrathin PFN-Br layer, prepared by spin coating at a rotation speed of 3000 rpm for 50 s followed by annealing at 90°C for 10 min. The use of PFN-Br-modified ITO anode is to create an interface dipole (25), assisting in bidirectional tunneling hole injection in the PM OPD. Then, a 300-nm-thick binary blend layer of P3HT: PC 70 BM (100:1) was deposited on the PFN-Br-modified ITO/glass substrates by spin coating at a rotation speed of 400 rpm for 100 s and annealing at 80°C for 20 s. A 320-nm-thick pristine P3HT optical spacer and a 500-nm-thick ternary blend layer of P3HT:PTB7-Th: PC 70 BM (70:30:1) were first coated on the precleaned silicon (Si) wafers, respectively.…”
Section: Device Fabricationmentioning
confidence: 99%
“…Notably, the conducting polymer counter electrode showed comparable device efficiency with the Pt counter electrode. In the past few years, a dozen of research groups reported high PCEs of >10% for ST-OSCs by using simple ultrathin metal top electrodes, which were attributed to the remarkable achievements of highly efficient narrow-bandgap polymer donors and Efficiency 67 cd A −1 [135] 72.4% [219]a) 15.3% [115] 2.7 cd A −1 [233] -2.2 cd A −1 [122,123] 14.3% [126] T-QLEDS AVT 84% 45% -----Efficiency 10.63% [244] 1.79 cd A −1 [247] 1.55 cd A −1 [249] ---0.19% [251] T-PeLEDs AVT -47.2% -----Efficiency -1.21% [252] -----ST-DSSCs AVT ----80% b) --PCE -6% [264] 3.6% [259] 6.54% [271] 9.1% [268] --ST-OSCs AVT 34% 30% 40% --60% b) 40% PCE 4% [297] 10.02% [304] 8.02% [298] 2.7% [174,175] -4.1% [317] 3.4% [321] ST-PeSCs AVT -22% -7.3% --20% PCE 16.3% [322] 13.6% [327] 11.07% [338] 10.1% [340] -9.9% [341] 12% [342] a)…”
Section: Discussionmentioning
confidence: 99%
“…Reproduced with permission. [ 249 ] Copyright 2018, The Royal Society of Chemistry. e) Schematic fabrication process, the current efficiency–voltage–EQE characteristics for T‐QLED with a laminated graphene anode.…”
Section: Transparent Light‐emitting Diodesmentioning
confidence: 99%
See 1 more Smart Citation
“…The emissive layer is a key component of light‐emitting devices, as it determines the electroluminescence (EL) performance (i.e., brightness, device efficiency, and color of emitted light (i.e., EL spectra)) of the device. Various emissive materials such as organic materials, [ 102–111 ] QDs, [ 15–17,112–116 ] and perovskite materials [ 117–120 ] have been employed for the fabrication of transparent light‐emitting diodes (LEDs) to acquire highly vivid colors with excellent brightness. Figure a,b compares the color characteristics of previously reported transparent LEDs with regard to the color gamut of the Commission internationale de l'éclairage (CIE) 1931 color coordinates and FWHMs of the EL spectra, respectively.…”
Section: Next‐generation Display Technologies For Extended Realitymentioning
confidence: 99%